Extraction and characterization of oil from the pulp of pequi (Caryocar brasiliense) produced manually in the allotment Piauzinho Municipality of Pium - TO (Research, Society and Development, 2022)
Research with the oil extracted from pequi can collaborate with the improvement of the extraction process, commercialization and generation of employment and income of this extractive activity. The objective of this work was the biometric characterization of the fruit and physicochemical analysis of the oil extracted from the pequi pulp produced by hand in the Piauzinho TO subdivision, comparing the results obtained in research carried out in the Tocantins region. An experimental study was carried out by harvesting the fruits and extracting the oil from the pequi pulp in the field. The physicochemical analyzes of the oil were carried out in the laboratory of the Federal Institute of Food Science and Technology Education - IFTO, Paraíso do Tocantins campus. The fruits were harvested, selected and transported for analysis in the laboratories. The results of the physical-chemical and biometric analyzes were submitted to analysis of variance. There were significant differences by Tukey's test (p < 0.05) in fruits and oils. The studied fruits show increases of 16.1% in height, 4.3% to 14.7% in longitudinal diameter, 3.5% to 21.2% in equatorial diameter, 3.6% to 36.7%, in fruit mass and 7.9% to 35.9% in the number of pyrenes in relation to the literature. The extracted oil presented density, acidity, peroxide and saponification with lower values ​​and higher humidity and viscosity than those found in the literature. The oil analyzed in the study presented values ​​for acidity and peroxide indexes within the established by current legislation and can be consumed and applied as raw material in industrial applications.